ANALISIS KINERJA ORGANISASI SUKU DINAS SOSIAL JAKARTA BARAT DALAM IMPLEMENTASI PROGRAM REHABILITASI SOSIAL TERHADAP GELANDANGAN PENGEMIS - Naro Sesa, Saytio; Hanani, Retna; Zarkasyi Rahman, Amni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Homelessness and beggars are a social problem. The city of West Jakarta experiences an increase in the number of homeless people and beggars every year. Therefore, the aim of this research is to analyze the organizational performance of the West Jakarta Social Service in implementing social rehabilitation programs to reduce the number of homeless people and beggars, as well as analyzing the factors that influence the organizational performance of the West Jakarta Social Service in implementing social rehabilitation programs using organizational performance measurement theory. according to Dwiyanto which includes productivity, service quality, responsiveness, responsibility, accountability, and the theory of factors that influence organizational performance using Mahmudi's theory, namely team factors, system factors and contextual factors. The method used is a descriptive qualitative method. The results of this research show that the performance of the West Jakarta Social Service Department is running well even though there are indicators that are not yet optimal, namely productivity and the factors that can influence the performance of the Social Service Department in implementing social rehabilitation programs are team factors, system factors and contextual factors. Of these three factors, the ones that hinder the performance of the West Jakarta City Social Service Department in implementing social rehabilitation programs are system factors and also contextual factors.